Method for measurement of all-color video signal peak signal-to-noise ratio - K.M. FELLGUSON (2010)
A method of measuring peak signal to noise ratio (PSNR) of full color video, both total and component contributions as well as providing PSNR full color and component maps includes converting the components of the full color video for both reference and impaired video signals to GBR values, and computing the error energy for each of the G, B and R channels between the reference and impaired videosignals. Each component contribution to the error for the full color video components is assessed by setting the other components to a reference value, such as zero. Also the total full color PSNR iscomputed in GBR. Finally a color residual PSNR map is generated and displayed together with the computed PSNR results to enable a user to visualize where the significant impairments occur in the impaired video.